Mechanical Cold Stimulus Helps Release of PDGF from Platelet Granules: A Pilot Study - Talukder, Biplabendu; Choudhury, Sunirmal; Saha, Soumen; Samanta, Sambit; Chakraborty, Rajib; Bhattacharya, Prasun (Annals of Pathology and Laboratory Medicine, 2025)
Background: Platelets are produced and released into the bloodstream by megakaryocytes, which reside within the bone marrow. It is pivotal in healing, hemostasis, and inducing inflammatory responses. Platelet-derived growth factor (PDGF), a critical cytokine, is released from the alpha granules of platelets and plays a significant role as a stimulator of cell division, blood vessel proliferation, and the proliferation of mesenchymal cells, including fibroblasts, osteoblasts, and vascular smooth muscle cells. PDGF also plays a role in inducing inflammation and promoting wound healing. Aims and Objectives: The study aimed to assess the PDGF concentration in PRP at 24°C and 4°C following cold stimulation. Methods: A total of 24 healthy volunteers participated in this study. A 10 mL blood sample was collected from their antecubital vein using a citrated Vacutainer in an aseptic manner. Four samples were discarded due to hemolysis, and six due to a low platelet count. Fourteen PRP samples were aliquoted into two parts for PDGF estimation at room temperature (22±2°C) and after cold stimulation at 4°C for 10 min using the sandwich ELISA method. Results: Semi-quantitative estimation of PDGF in normal (room temperature) and at 4°C shows a significant difference in OD value (P<0.001). PDGF value showed a moderate, positive correlation with the platelet number in PRP. Conclusion: The study concluded that cold exposure was strongly correlated with an increase in platelet count and PDGF concentration, which may explain the initiation of growth factor-induced rapid wound healing in cold-compressed traumatic injuries in local areas.